Statistical design of ultra-thin SiO2 for nanodevices - Hashim.U; Abul Fatah M.F.A; Ahmad I; Majlis B.Y (Universiti Kebangsaan Malaysia, 2009)
A study was performed on a series of ultra thin SiO2 films in order to determine the factors affecting the oxide growth and also the effect of temperature to the film surface roughness. The samples of ultra thin SiO2 were prepared through a dry oxidation method using a high temperature furnace. There are three levels of temperature used, that is 900, 950 and 1000°C and the samples were grown at 0.333 litre/min, 0.667 liter/min and 1 liter/min oxygen flow rate and different oxidation times of 1, 2 and 3 minutes. The thickness was determined using an ellipsometer and the micro morphology of the oxide surface was obtained by using an atomic force microscope (AFM). The thickness of the oxide ranged from 1 to 5 nm. All the data has been interpreted using Taguchi’s method to analyze the most affecting factors in producing an ultra thin silicon dioxide. The optimum parameters are 900°C, 0.333 litre/min and at 1 minute time. The most influential parameter is temperature. The temperature also affects the surface roughness. The AFM result of 950°C with RMS value of 0.1088 nm is better than the 900°C oxide with RMS value 0.4553 nm. This shows that oxides need to be grown at a higher temperature to provide better surface roughness which is also important in ultra thin gate oxide characteristics.